2020
DOI: 10.1111/nyas.14485
|View full text |Cite
|
Sign up to set email alerts
|

A novel treatment for skin repair using a combination of spironolactone and vitamin D3

Abstract: Injury of the skin from exposure to toxic chemicals leads to the release of inflammatory mediators and the recruitment of immune cells. Nitrogen mustard (NM) and other alkylating agents cause severe cutaneous damage for which there are limited treatment options. Here, we show that combined treatment of vitamin D3 (VD3) and spironolactone (SP), a mineralocorticoid receptor antagonist, significantly improves the resolution of inflammation and accelerates wound healing after NM exposure. SP enhanced the inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…In the present study, we used the MEVM to investigate cutaneous responses to HN2. We observed and confirmed that 24 hr after a single topical application of HN2, mouse ear skin exhibited massive immune cell infiltration, necrosis, increased TUNEL activity (an indicator of DNA injury), an upregulation of the tissue injury-associated matrix metalloproteinase 9 (MMP-9) ( Cuffari et al, 2018 , Kumar et al, 2015 , Tumu et al, 2020 , Wormser et al, 2002 ) and an increased tissue presence of the proinflammatory enzyme inducible nitric oxide synthase (iNOS) ( Biyashev et al, 2020 , Composto et al, 2016 , Kumar et al, 2015 , Tumu et al, 2020 ). MMP-9 is a proteolytic enzyme capable of degrading extracellular matrix proteins such as denatured collagen (gelatin) and collagen types IV, V, VII, IX and X ( van der Jagt et al, 2006 ).…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…In the present study, we used the MEVM to investigate cutaneous responses to HN2. We observed and confirmed that 24 hr after a single topical application of HN2, mouse ear skin exhibited massive immune cell infiltration, necrosis, increased TUNEL activity (an indicator of DNA injury), an upregulation of the tissue injury-associated matrix metalloproteinase 9 (MMP-9) ( Cuffari et al, 2018 , Kumar et al, 2015 , Tumu et al, 2020 , Wormser et al, 2002 ) and an increased tissue presence of the proinflammatory enzyme inducible nitric oxide synthase (iNOS) ( Biyashev et al, 2020 , Composto et al, 2016 , Kumar et al, 2015 , Tumu et al, 2020 ). MMP-9 is a proteolytic enzyme capable of degrading extracellular matrix proteins such as denatured collagen (gelatin) and collagen types IV, V, VII, IX and X ( van der Jagt et al, 2006 ).…”
Section: Introductionmentioning
confidence: 52%
“…Our lab ( Cuffari et al, 2018 , Tumu et al, 2020 ) and others ( Kumar et al, 2015 , Wormser et al, 2002 ) have found that HN2 increases the expression of MMP-9 in mouse skin. In addition, we ( Tumu et al, 2020 ) and others ( Biyashev et al, 2020 , Composto et al, 2016 , Kumar et al, 2015 ) have observed that HN2 increases the tissue expression of inducible nitric oxide synthase (iNOS) in mouse skin, which, in turn, is important for generating cytotoxic levels of nitric oxide in the skin ( Composto et al, 2016 , Nguyen and Soulika, 2019 ). Moreover, we have also reported that a significant increase in TUNEL positive cells occurs in mouse ear skin treated with HN2 ( Tumu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…Our results shown here may therefore be somewhat artificial due to the vehicle employed in our work. Nonetheless, as research is underway at improving the delivery of SP into the skin (Abdel-Raouf et al 2021;Abdel-Raouf et al 2020;Biyashev et al 2020;Ilic et al 2021;Kelidari et al 2017;Kelidari et al 2016;Kelidari et al 2015;Salama et al 2019), we suggest that care may need to be taken to ensure that such approaches do not induce toxicity or cause a reduction in XPB protein expression, which could interfere with UV photoproduct removal and increase the risk of skin carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Though SP has traditionally been used as an oral medication, there has been an interest in developing alternative formulations (Abdel-Raouf et al 2021;Abdel-Raouf et al 2020;Biyashev et al 2020;Ilic et al 2021;Kelidari et al 2017;Kelidari et al 2016;Kelidari et al 2015;Salama et al 2019) that can be applied topically on the skin for beneficial purposes and to avoid the systemic effects that usually limit its use to females (Bowman et al 2012). In addition, because glucocorticoids can induce skin atrophy and inhibit wound healing due to aberrant stimulation of mineralocorticoid receptors, SP and related MR antagonists have been employed in experimental studies in mouse models and human subjects to counteract some of the negative effects of glucocorticoids (Boix et al 2018;Maubec et al 2015;Nguyen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, also spironolactone in combination with vitamin D3 has been shown to inhibit NF-κB activity in mouse macrophages and further decrease the expression of proinflammatory cytokines in a skin injury model [ 60 ]. Importantly, the inhibition of NF-κB by spironolactone was shown to be independent of the mineralocorticoid receptor [ 61 ].…”
Section: Potential Pharmacological Actions Of Spironolactone In Comentioning
confidence: 99%